Construction of an information model of the digital twin of the technological process in a power unit at a nuclear power plant - Budanov, Pavlo; Brovko, Kostiantyn; Melnikov, Vyacheslav; Yakymchuk, Mykola; Kononov, Volodymyr; Kyrysov, Ihor; Nosyk, Andrii; Karpenko, Oleh; Kalnoy, Sergiy; Khomiak, Eduard (Eastern-European Journal of Enterprise Technologies, 2025)
This study's object is the technological process that occurs at the power unit of a nuclear power plant, which is considered as a complex technical system with a multi-level hierarchical structure of functional subsystems. This paper addresses the task to improve the efficiency of modeling, monitoring, and controlling the technological process at a nuclear power plant as a complex technical system with a multi-level hierarchical structure. A new approach to modeling the modes of a nuclear power plant based on system-cluster theory has been proposed. A cluster structure with key subclusters has been built: power control, protection, heat carrier adjustment, and emergency shutdown. Mathematical models have been constructed that take into account physical processes and logical-dynamic behavior of the monitoring and control system. A feature of the devised approach is the use of the value of fractal dimensionality as a quantitative indicator of the self-similar scaled structure of functional subclusters. An algorithm for calculating fractal dimensionality has been proposed, which allows for real-time analysis of dynamic changes in the external and internal structure of the power unit process control. Threshold values of the fractal dimensionality of subclusters have been determined for comparison with current parameters under normal and emergency modes. It was established that the loss of one control level in a subcluster leads to a decrease in fractal dimensionality from 1.83 to 1.60, signaling a possible degradation of the SCADA level. A model of a digital twin of the power unit process has been built based on a system-cluster approach, which allows for the implementation of visualization, simulation, monitoring, and diagnostics functions